A cross-sectional survey of reproductive, gynecological, and breast health histories and status among people in a provincial prison for women in British Columbia - Clare Heggie; Martha Paynter; Anja McLeod; Jessica Liauw; Rosann Edwards; Fiona Kouyoumdjian (PLoS ONE, 2026)
Objectives Women are a growing prison population in Canada, yet there is a lack of systematic data collection on the reproductive health of people incarcerated in prisons for women. The objective of this study was to describe a wide range of reproductive, gynecological, and breast health histories, including access to preventive services, among people incarcerated in a provincial prison for women in British Columbia. Study design A cross-sectional survey design was used to meet study objectives. Methods We adapted a survey instrument previously administered in four provincial prisons in Atlantic Canada. The survey consisted of 54 questions about demographics and reproductive, gynecological, and breast health. The survey was administered on paper, in person, and we analyzed data using descriptive statistics. Results Of 75 participants, 48% identified as Indigenous, with a median age of 36 years. Eighty-five percent of participants had ever been pregnant, 72% reported having had an unintended pregnancy and 51% had ever had an abortion. The most used types of contraception included the male condom and birth control pill. Among participants eligible for cervical cancer screening, 48% had a Pap test within the last 3 years. Of those eligible for screening based on age and provincial guidelines, 40% had ever had a mammogram. Conclusions Findings from this cross-sectional survey highlight health disparities when compared with people in the general community, underscoring the need for routine and systematic data collection on reproductive, gynecological and breast health history and outcomes in this population and the need for collaborative approaches to ensure incarcerated women have access to appropriate and recommended preventive healthcare services.